Preparation and characterization of carbon black (CB) using heavy residue fraction of spent tyre pyrolysis oil. Issue 6 (December 2021) - Okoye, Chiemeka Onyeka; Zhu, Mingming; Jones, Isabelle; Zhang, Juan; Zhang, Zhezi; Zhang, Dongke
Abstract: In the interest of utilisation of industrial waste products, this paper investigated the preparation and characterization of carbon black (CB) made via partial oxidation of a heavy residue fraction (HRF) of spent tyre pyrolysis oil in a drop tube furnace. The effect of process temperature, residence time (Rtime ), and O2 concentration on the yield and quality (elemental composition, functional groups, morphology, thermal behavior, and surface area) of HRF-CB were determined using elemental analyzer (EA), X-ray photoelectron spectroscopy (XPS), transmission electron microscopy (TEM), thermogravimetric analyzer (TGA), and Brunauer-Emmett-Teller (BET) nitrogen adsorption/desorption technique. Higher temperatures led to higher yields (41–60%) and better quality of the resultant CB. Above 1150 °C, the CB samples were comparable with commercial CB products, with low ash (<0.1%), low volatile matter (<6.1%), moderate BET surface area (11–24.2 m 2 g −1 ), and high C contents (~94–99%). Quality was also improved as Rtime or O2 increased but at some sacrifice to the total yield. HRF-CB aggregates were morphologically complex, highly structured and had good thermal stability, which increased with increasing process temperature, Rtime and O2 concentration, respectively. Interestingly, the hydroxyl, carbonyl and carboxyl surface groups in the HRF-CB were higher (54 – 69%) than commercial products (0–59%) under all process conditions, which is a desirable trait for enhanced bonding and mechanical properties but typically introduced to commercial CB by secondary procedures. Given their comparable properties, CB from heavy residues of spent tyre pyrolysis oil may be a suitable replacement for commercial CBs used in rubber reinforcement. Graphical Abstract: ga1 Highlights: Carbon black (CB) was successfully made from heavy residue of spent tyre oil. CB yield is mostly determined by the process temperature and residence time. CB quality is enhanced by increasing the process temperature and O2 concentration. The CB aggregates have high structure with complex shape configuration.